Examining Project Management Maturity: The Case Study of a Leading Company in Energy Sector - Gonsior, Michał (Badanie dojrzałości zarządzania projektami: studium przypadku wiodącej firmy z sektora energetycznego, 2023)
Management Maturity and highlight the potential benefits of conducting such diagnostics. Design/Methodology/Approach – first the article presents a summary of the literature review, introducing the concept of Project Management Maturity and describing the most popular models available in the field. The author also provides the results of a research conducted in a leading Polish energy player, using a case study method with individual in-depth interviews as the main data gathering technique. Findings – the study suggests that Project Management Maturity assessment can lead to multiple meaningful insights when conducted in a business. This could lead to significant efficiency improvements to the Project Management function within the company. Originality of the research – the article offers an insightful summary of a diagnosis conducted in a large energy player, presenting a brief description of the internal organization of the Project Management function. The results are useful for scholars and professionals who are interested in the topic of Project Management Maturity assessments, and would like to appreciate insights generated by the study.
s. 24-38
Keywords: project management maturity; project management in energy sector; evaluation model; project maturity; dojrzałość zarządzania projektami; zarządzanie projektami; zarządzanie projektami w energetyce; model oceny; dojrzałość projektowa